An ultrasound activated cyanine-rhenium(i) complex for sonodynamic and gas synergistic therapy - Zhu J.; Ouyang A.; He J.; Xie J.; Banerjee S.; Zhang Q.; Zhang P. (My University, 2025)
A novel cyanine-rhenium(i) tricarbonyl complex is developed as a potent sonosensitizer and sono-activatable CO-releasing agent for synergistic sonodynamic therapy and CO gas therapy of cancer. The complex induced ferroptosis as the mode of cell death. © The Royal Society of Chemistry